Kajian Ikonografi Ornamen pada Interior Masjid Cheng Hoo Surabaya - Tasha Victoria Tanaja; Lintu Tulistyantoro (Intra, 2017)
Cheng Hoo Mosque Surabaya is a Chinese architecture that is identical with the octagonal roof arrangement that is, Pat Kua strengthen the character of Chinese architecture. This is the main attraction of Cheng Hoo Mosque Surabaya, especially the interior ornaments used in the mosque to be studied by descriptive qualitative method described by Panofsky iconography theory. This theory has three stages: pre-iconography, iconographic analysis, and iconographic interpretation.The pre-iconography stage describes the interior ornaments used in the mosque through field data and interview results. An analysis iconography explains the meaning contained in the interior ornaments used from the literature data. The iconographic interpretation discusses the interrelation of the building with the political, social and cultural conditions in Indonesia. The results show the uniqueness of architecture and interior ornate Islamic Islam of China, and has a philosophical meaning.